Pengaruh Dukungan Sosial terhadap Work Family Conflict pada Polwan - Nabila Sahira Bilqis; Anna Rozana (UNISBA Press, 2023)
Work family conflict is related to negative behavior at work and it is a source of stressor that result into unwanted negative effect (Higgins, Duxbury, & Irving, 1992). Social support has become an important coping mechanism and source in reducing negative effect resulted from work family conflict (Ayman & Antani, 2008). Occupation such as Female police officers shows the need of social support to overcome work family conflict due to their simultaneous role as a housewife and a police officer (Almasitoh, 2011). The purpose of this study was to examine how social support has an impact on work family conflict for female police officer. This research is classified as a quantitative research using causal method. The population in this research are 163 female police officers who are assigned to Polda DIY and has qualified for the criteria for this research, so that simple random sampling method can be used with the respondent of 116 female police officer as subjects. The analytical technique in this research uses multiple linear regression. The measuring instrument used within this research are the work family conflict scale created by Carlson & Kacmar which has been translated to Indonesian by Kuntari (2014) and the social support measurement developed by Parasuraman based on House (1983) theory which has been adapted by Nindyasari (2015). The results showed that social support had a significant negative effect on work family conflict among policewomen at Polda DIY by 51.4% and the greatest influence on work family conflict was social support from spouseses at 29.4%. Work family conflict terkait dengan sikap kerja negatif dan merupakan sumber stressor yang memberikan efek negatif yang tidak diinginkan (Higgins, Duxbury, & Irving, 1992). Dukungan sosial merupakan mekanisme koping penting yang dapat mengurangi efek negatif dari work family conflict dan merupakan sumber positif yang sangat diperlukan dalam menurukan work family conflict (Ayman & Antani, 2008). Polwan membutuhkan adanya dukungan sosial untuk mengatasi work family conflict yang dialami dari adanya ketidakseimbangan antara peran sebagai pekerja dan peran sebagai ibu rumah tangga (Almasitoh, 2011). Tujuan dari penelitian ini adalah untuk menguji seberapa besar pengaruh dukungan sosial terhadap work family conflict pada polwan. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan metode kausalitas. Populasi dalam penelitian ini adalah 163 polwan di Polda DIY yang telah memenuhi kriteria yang diambil menggunakan teknik simple random sampling dengan jumlah responden sebanyak 116 polwan. Teknik analisis yang digunakan adalah uji regresi linear berganda. Alat ukur yang digunakan adalah Work-family conflict scale dari Carlson & Kacmar yang telah diadaptasi oleh Kuntari (2014) dan alat ukur dukungan sosial yang dikembangan oleh Parasuraman dengan berdasarkan acuan dari teori House (1983) yang telah diadaptasi oleh Nindyasari (2015). Hasil penelitian menunjukkan bahwa dukungan sosial berpengaruh negatif signifikan terhadap work family conflict pada polwan di Polda DIY sebesar 51,4% dan pengaruh paling besar terhadap work family conclict adalah dukungan sosial pasangan sebesar 29,4%.